Cognitive screening and depressive symptoms in hypertensive and diabetic women - de Paiva Novais, Iane; Stein, Angelica Miki; de Almeida, Sarah Costa; da Silva, Thays Martins Vital; da Silva, Luzia Wilma Santana; Zanesco, Angelina [UNESP] (My University, 2022)
Aim: The objective of this study was to compare the global cognitive function and depressive symptoms in hypertensive and/or diabetic middle-aged and elderly women (52-76 years old). Methods: Sixteen participants with hypertension (HT) and 12 with hypertension and type 2 diabetes mellitus (HT+DM) were included; sociodemographic data, anthropometric measurements, and blood pressure were analyzed, and questionnaires for cognitive screening (Mini-Mental State Examination - MMSE) and depressive symptoms (Geriatric Depression Scale - GDS-30) were administered. For statistical analysis, independent Student's t-test, chi-square test (dichotomous variables), and the Mann-Whitney test (ordinal variables) were used and p < 0.05 was adopted. Results: Results indicate that there were no significant differences pertaining to depressive symptoms (HT = 7.4 ± 5.5; HT+DM = 10.2 ± 4.6 points; p = 0.1658) and global cognitive function (HT = 22.3 ± 4.2; HT+DM = 21.0 ± 3.2 points; p = 0.4015) between hypertensive women and hypertensive and diabetic women, contradicting the hypothesis that the presence of two comorbidities would intensify cognitive impairment and mental health. However, clinically relevant cognitive decline (HT = 63%; HT+DM = 75%; χ2 = 0.4834) and depressive symptoms (HT = 38%; HT+DM = 33%; χ2 = 0.8199) were found in both groups. Conclusion: It has been shown that the presence of two comorbidities: type 2 diabetes mellitus and hypertension, does not intensify cognitive impairment and mental health when compared to hypertension alone in middle-aged and elderly women.
Keywords: Cognitive function; Comorbidity; Elderly; Hypertension; Type 2 diabetes mellitus